Farmer Children’s Willingness for Dairy Farming succession in Banyumas Regency - Krismiwati Muatip; Moch Sugiarto (Animal Production: Indonesian Journal of Animal Production, 2016)
The objectives of this research were to 1) observe the age, education, farm parents’ cattle ownership, parents’ income, children’s perception and willingness for farming succession, and 2) investigate the relationship between age, education, farm parents’ cattle ownership, parents’ income, children’s perception of and willingness for farming succession. Purposive sampling was used to determine the regional sample in three districts in Banyumas regency with the most dairy cow population and were the supervised area subject to “Pesat” Milk Cooperative. Ninety respondents from 10-30 years old were determined. Result showed that farmers’ children had better education than the parents with average age of 21,67 years old. Average cattle ownership was 1-15 heads per household with Rp 564.167 – Rp 4.523.333monthly income. Farmers’ children shaped positive perception on dairy farming and had willingness for farming succession. Age was positively correlated with farming perception and willingness of the farmers’ children, while education was negatively correlated.